SHAHEILA BT HAJI ABDUL MAJID LWN. ROSLAN B. ABDUL AZIZ - Wilayah Persekutuan, Mahkamah Rendah Syariah (Jurnal Syariah, 2019)
Muslim Family law - Application for ta’liq divorce - Husband leaved house - Failed to provide maintenance to wife - Husband beat wife - Muslim Family Law Act (Wilayah-Wilayah Persekutuan) 1984, section 50.